Hey there!
<u>Use the quadratic formula to find the solution(s). x² + 2x - 8 = 0</u>
x = -4 or x = 2 ✅
<em><u>Quadratic</u></em><em><u> </u></em><em><u>formula </u></em><em><u>:</u></em><em><u> </u></em>ax² + bx + c = 0 where a ≠ 0
The number of real-number solutions <em>(roots)</em> is determined by the discriminant (b² - 4ac) :
- If b² - 4ac > 0 , There are 2 real-number solutions
- If b² - 4ac = 0 , There is 1 real-number solution.
- If b² - 4ac < 0 , There is no real-number solution.
The <em><u>roots</u></em> of the equation are determined by the following calculation:
![x = \frac{ - b \pm \sqrt{ {b}^{2} - 4ac } }{2a}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B%20-%20b%20%5Cpm%20%20%5Csqrt%7B%20%7Bb%7D%5E%7B2%7D%20-%204ac%20%7D%20%7D%7B2a%7D%20)
Here, we have :
1) <u>Calculate </u><u>the </u><u>discrim</u><u>i</u><u>n</u><u>ant</u><u> </u><u>:</u>
b² - 4ac ⇔ 2² - 4(1)(-8) ⇔ 4 - (-32) ⇔ 36
b² - 4ac = 36 > 0 ; The equation admits two real-number solutions
2) <u>Calculate </u><u>the </u><u>roots </u><u>of </u><u>the </u><u>equation</u><u>:</u>
▪️ (1)
![x_1 = \frac{ - b - \sqrt{ {b}^{2} - 4ac} }{2a} \\ \\ x_1 = \frac{ - 2 - \sqrt{36} }{2(1) } \\ \\ x_1 = \frac{ - 2 - 6}{2} \\ \\ x_1 = \frac{ - 8}{2} \\ \\ \blue{\boxed{\red{x_1 = -4}}}](https://tex.z-dn.net/?f=x_1%20%3D%20%20%5Cfrac%7B%20-%20b%20-%20%20%5Csqrt%7B%20%7Bb%7D%5E%7B2%7D%20%20-%204ac%7D%20%7D%7B2a%7D%20%20%5C%5C%20%20%5C%5C%20x_1%20%3D%20%20%5Cfrac%7B%20-%202%20-%20%20%5Csqrt%7B36%7D%20%7D%7B2%281%29%20%7D%20%20%5C%5C%20%20%5C%5C%20x_1%20%3D%20%20%5Cfrac%7B%20-%202%20-%206%7D%7B2%7D%20%20%20%5C%5C%20%5C%5C%20x_1%20%3D%20%20%5Cfrac%7B%20-%208%7D%7B2%7D%20%20%5C%5C%20%20%5C%5C%20%5Cblue%7B%5Cboxed%7B%5Cred%7Bx_1%20%3D%20-4%7D%7D%7D)
▪️ (2)
![x_2 = \frac{ - b + \sqrt{ {b}^{2} - 4ac } }{2a} \\ \\ x_2 = \frac{ - 2 + \sqrt{36} }{2(1)} \\ \\ x_2 = \frac{ - 2 + 6}{2} \\ \\ x_2 = \frac{4}{2} \\ \\ \red{\boxed{\blue{x_2 = 2}}}](https://tex.z-dn.net/?f=x_2%20%3D%20%20%5Cfrac%7B%20-%20b%20%20%2B%20%20%20%5Csqrt%7B%20%7Bb%7D%5E%7B2%7D%20-%204ac%20%7D%20%7D%7B2a%7D%20%20%5C%5C%20%20%5C%5C%20x_2%20%3D%20%20%5Cfrac%7B%20-%202%20%2B%20%20%5Csqrt%7B36%7D%20%7D%7B2%281%29%7D%20%20%5C%5C%20%20%5C%5C%20x_2%20%3D%20%20%5Cfrac%7B%20-%202%20%2B%206%7D%7B2%7D%20%20%5C%5C%20%20%5C%5C%20x_2%20%3D%20%20%5Cfrac%7B4%7D%7B2%7D%20%20%5C%5C%20%20%5C%5C%20%5Cred%7B%5Cboxed%7B%5Cblue%7Bx_2%20%3D%202%7D%7D%7D)
>> Therefore, your answers are x = -4 or x = 2.
Learn more about <u>quadratic equations</u>:
brainly.com/question/27638369
Since the sequence is geometric, there is some constant
![r](https://tex.z-dn.net/?f=r)
such that the sequence is recursively given by
![a_n=ra_{n-1}](https://tex.z-dn.net/?f=a_n%3Dra_%7Bn-1%7D)
By this definition, you can recursively substitute into the right hand side the definition for
![a_{n-1},a_{n-2},\ldots](https://tex.z-dn.net/?f=a_%7Bn-1%7D%2Ca_%7Bn-2%7D%2C%5Cldots)
to find an explicit formula for the
![n](https://tex.z-dn.net/?f=n)
th term.
![a_n=ra_{n-1}=r^2a_{n-2}=r^3a_{n-3}=\cdots=r^{n-1}a_1=-625r^{n-1}](https://tex.z-dn.net/?f=a_n%3Dra_%7Bn-1%7D%3Dr%5E2a_%7Bn-2%7D%3Dr%5E3a_%7Bn-3%7D%3D%5Ccdots%3Dr%5E%7Bn-1%7Da_1%3D-625r%5E%7Bn-1%7D)
You know the second term, which means you can find
![r](https://tex.z-dn.net/?f=r)
:
![a_2=-625r^{2-1}\implies125=-625r\implies r=-\dfrac15](https://tex.z-dn.net/?f=a_2%3D-625r%5E%7B2-1%7D%5Cimplies125%3D-625r%5Cimplies%20r%3D-%5Cdfrac15)
So, the 7th term of the sequence is
Answer:
2/12
Step-by-step explanation:
4w=2/3
1/4(4w)=1/4 x 2/3
w=2/12
9514 1404 393
Answer:
A. √13
Step-by-step explanation:
You can make an educated guess and come to the right conclusion.
The triangle is nearly an equilateral triangle. A triangle with two sides 3 and an angle of 60° would have a third side of 3. A triangle with two sides of 4 and an angle of 60° would have a third side of 4.
So, the third side must be between 3 and 4. Here is an evaluation of the answer choices:
__
A -- between 3 and 4, the correct choice
B -- 3, too short
C -- 1.73, too short
D -- more than 4, too long
__
The question can be answered using your triangle solver app on your calculator, or using the Law of Cosines.
c = √(a^2 +b^2 -2ab·cos(C))
c = √(3^2 +4^2 -2·3·4·(1/2)) = √(9 +16 -12)
c = √13 . . . . . length of the side opposite the 60° angle
Answer:
Step-by-step explanation:
[2,∞)